Effects on Processed Geopolymer Concrete with Respect to Different Strength Parameters - Bhat, Mohammad Mujeeb Ur Rehman (AMC Indian Journal of Civil Engineering, 2019)
The objective of this study is to study the effects of partial replacement of MIRHA on processed flyash as a geopolymer concrete, and it is compared with the unprocessed flyash and plain cement concrete. The strength of plain cement concrete increases gradually from 3 to 28 days of water curing. The strength of processed and rice husk ash processed flyash geopolymer concrete mixes gains early strength within 3 days of curing and later increases only by 20 to 25 % at the end of 28 days of curing. The strength of rice husk ash processed flyash geopolymer concrete mixes increases from 2% to 3% replacement, and beyond 5% replacement, the strength starts decreasing. 3% rice husk ash processed flyash geopolymer concrete gives the maximum value of compressive strength as compared to other mixes. As the percentage of rice husk ash is changed from 2% to 10%, the flyash to alkaline activator ratio goes on decreasing from 0.66 to 0.43. The more the rice husk is replaced, less will be flyash to alkali activator ratio, but there will be decrease in strength.